Pengaruh guru dalam mengatasi kesulitan siswa pada proses pembelajaran - Nawangwulan, Septiyanisa Sekar (Maliki Interdisciplinary Journal, 2024)
Learning difficulties are problems that teachers encounter during learning because it is the responsibility of a teacher to overcome them. The emergence of difficulties in the learning process is caused by the failure of students to absorb lessons properly. It is very important for teachers to overcome student learning difficulties and is very influential in student education. Simply put, a teacher is an educator whose job is to guide, teach, and train students. In this study I used the library research method by reading, studying, and researching books that have a relationship and attachment to the role of the teacher in the success of the learning process. Data obtained and collected from library research, among others, from various sources that support research data, can be from reference books, journals, articles, papers, and other sources. Based on the results of the research, being a teacher or educator is already required to make teaching concise with curriculum goals arranged and implemented with many fun and not boring teaching models, so that in the learning process students are excited, motivated to learn, and the content of the material explained by the teacher can be understood.